Potato crop health quality and yield losses in Ecuador - Navarrete, I.; Panchi, N.; Andrade-Piedra, J.L. (2017)
The poor knowledge about the presence of diseases and pests affecting the potato crop in developing countries difficult the understanding of their distribution in agro-ecological systems and consequent effect on yield and seed quality. A combination of a monitoring and a field experiment were performed to: (1) determine the incidence and severity of pathogens and pests affecting foliage and seed tubers, (2) determine the influence of altitude and seed sources over seed quality, and (3) determine yield responses to seed quality. Disease and pest monitoring on the foliage and seed tubers was performed in farmers’ fields in the main potato production provinces in Ecuador in 2010. The field experiment was performed in CIP-Quito by planting the evaluated seed tubers from 2010-2011 and registering their individual yield. We found that late blight and flea beetle damages were constantly affecting foliage, whereas black scurf, andean weevil, potato virus S and potato virus X predominantly affected seed tubers. Our data suggest that planting at higher altitudes potentially reduce seed-borne viral diversity, and that pathogens and pests diversity on farmers’ seed tubers is similar regardless the seed source. Yield variation was explained by the following problems in the seed tuber: black scurf, presence of potato virus S, potato yellow vein virus, and presence of mechanical damages. However, these problems varied when seed source or variety changed.